2016
DOI: 10.1016/j.labeco.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Sex, drugs, and ADHD: The effects of ADHD pharmacological treatment on teens' risky behaviors

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…One population that might experience a decline in injury in response to the switch to MMC are children with ADHD. In this population, medication has been shown to have positive effects in terms of reducing the risk of injury (Chorniy and Kitashima, 2016;Dalsgaard et al, 2014). Panels F and G examine the subsample of children who had at least one visit or prescription for ADHD over the entire sample period.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One population that might experience a decline in injury in response to the switch to MMC are children with ADHD. In this population, medication has been shown to have positive effects in terms of reducing the risk of injury (Chorniy and Kitashima, 2016;Dalsgaard et al, 2014). Panels F and G examine the subsample of children who had at least one visit or prescription for ADHD over the entire sample period.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…The vast majority of children diagnosed with ADHD receive medication, with some also receiving behavioral therapies. Many studies have shown short-term improvements in attention and decreases in disruptive behavior in medicated children, though the longer-term effects of medication for ADHD are more controversial (Scheffler et al, 2009;Visser et al, 2014;Currie et al, 2014;Dalsgaard et al, 2014;Chorniy and Kitashima, 2016). Although research is ongoing, the bulk of the evidence suggests that ADHD medication affects behavior in a way that may improve safety and health outcomes, however there is little evidence of long-term improvements in academic performance.…”
Section: Characteristics Of Adhd and Asthmamentioning
confidence: 99%
“…Finally, given previous evidence that treatment for ADHD can reduce ER visits and hospitalization for injuries (Chorniy and Kitashima, 2016; Dalsgaard et al, 2014) we also examine the effect of MMC on these outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…The vast majority of children diagnosed with ADHD receive medication, with some also receiving behavioral therapies. Many studies have shown short-term improvements in attention and decreases in disruptive behavior in medicated children, though the longer-term effects of medication for ADHD are more controversial (Scheffler et al, 2009; Visser et al, 2014; Currie et al, 2014; Dalsgaard et al, 2014; Chorniy and Kitashima, 2016; Kitashima and Chorniy, 2017). …”
Section: Data and Backgroundmentioning
confidence: 99%
“…Dalsgaard, Nielsen, and Simonsen () find that among those diagnosed with ADHD, receiving medication treatment results in fewer hospital contacts. Chorniy and Kitashima () find that among children who have been diagnosed with ADHD with Medicaid coverage in South Carolina, those receiving medication treatment are less likely to engage in risky behaviors. Children with ADHD are much less likely to succeed in school and may find that inability to pay attention causes a reduction in human capital formulation (Currie & Stabile, ; Fletcher & Wolfe, ).…”
Section: Introductionmentioning
confidence: 99%